2022
DOI: 10.1371/journal.pmed.1004069
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in distribution of COVID-19 vaccines across US counties: A geographic information system–based cross-sectional study

Abstract: Background The US Centers for Disease Control and Prevention has repeatedly called for Coronavirus Disease 2019 (COVID-19) vaccine equity. The objective our study was to measure equity in the early distribution of COVID-19 vaccines to healthcare facilities across the US. Specifically, we tested whether the likelihood of a healthcare facility administering COVID-19 vaccines in May 2021 differed by county-level racial composition and degree of urbanicity. Methods and findings The outcome was whether an eligibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 15 publications
(18 reference statements)
2
19
0
Order By: Relevance
“…Decreased access to vaccination has been observed in minoritized, lower-income, or rural communities, as vaccine administration locations were less likely to exist in these areas in the early vaccine rollout process. [44] , [45] These access barriers are related to socioeconomic conditions, but are distinct influences on vaccine uptake and should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased access to vaccination has been observed in minoritized, lower-income, or rural communities, as vaccine administration locations were less likely to exist in these areas in the early vaccine rollout process. [44] , [45] These access barriers are related to socioeconomic conditions, but are distinct influences on vaccine uptake and should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…However, propensity scores have important limitations: in particular, they can only be used to achieve balance on measured variables, and not unmeasured confounders. Socioeconomic factors, such as race/ethnicity, education levels, and health insurance; residing in urban or rural areas; previously receipt of vaccinations; and political partisanship have been shown to affect not only vaccine hesitancy, but also vaccine availability [26][27][28] . It has also been shown that communities with lower education levels and greater percentages of black residents have higher rates of COVID-19 cases and fatalities 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Several pharmaceutical companies led a global race to develop vaccines, three of which were primarily available to Americans (Pfizer BNT162b2, Moderna mRNA-1273, and Janssen Ad26.COV2.S). Despite widespread geographic variations in vaccination rates, 3 6 substantial national efforts have effectively transitioned the pandemic to an endemic phase. 7 Today, with around 77% of the US adult population having completed primary series vaccination, weekly hospitalization rates have dropped from a national US average of 16,000 weekly admissions in January 2021 to around 3000 in October 2022.…”
Section: Introductionmentioning
confidence: 99%